Standardized Whole Blood Assay and Bead-Based Cytokine Profiling Reveal Commonalities and Diversity of the Response to Bacteria and TLR Ligands in Cattle - Lesueur, Jérémy; Walachowski, Sarah; Barbey, Sarah; Cebron, Nathan; Lefebvre, Rachel; Launay, Frédéric; Boichard, Didier; Germon, Pierre; Corbiere, Fabien; Foucras, Gilles (Frontiers in Immunology, 2022)
Recent developments of multiplex technologies enable determination of a large number of soluble proteins such as cytokines in various biological samples. More than the one by one determination of the concentration of immune mediators, they permit establishment of secretion profiles for a more accurate description of conditions related to infectious diseases, or vaccination. Cytokine profiling was recently made available for bovine species with the development of a Luminex® technology-based 15-plex assay. Independently from the manufacturer, we evaluated the bovine cytokine/chemokine multiplex assay for limits of detection, recovery rate and reproducibility. Furthermore, we assessed cytokine secretion in blood samples from 107 cows upon stimulation with heat-killed bacteria and TLR2/4 ligands compared to a null condition. Secretion patterns were analyzed either using absolute concentration of cytokines or using their relative concentration with respect to the overall secretion level induced by each stimulus. Using Partial Least Square-Discriminant Analysis, we show that the 15-cytokine profile is different under Escherichia coli, Staphyloccoccus aureus and Streptococcus uberis conditions, and that IFN-γ, IL-1β and TNF-α contribute the most to differentiate these conditions. The biological response induced by LPS and Escherichia coli were largely overlapping, but Staphyloccoccus aureus and Streptococcus uberis were associated with distinct cytokine profiles than their respective TLR ligands. Finally, results based on adjusted or absolute cytokine levels yielded similar discriminative power, but led to different stimuli-related signatures.